Effect of Nanocalcium Carbonate Content on the Properties of PLA Nanocomposites - Pundir, Ankit; Gopala Krishnan, P. Santhana; Nayak, Sanjay Kumar (Journal of Composites and Biodegradable Polymers, 2017)
Even though poly(lactic acid) is one of the most promising biodegradable polymers, less hydrophilic, low impact strength and heat resistance limits its applications. The current study was undertaken to overcome these limitations. Poly(lactic acid)-calcium carbonate nanocomposites were prepared by melt blending technique upto 3 wt. % using master batch containing 4 wt. % of nanocalcium carbonate content. Water absorption and density increased with increase in nanofiller content. Tensile and flexural strength and heat deflection temperature increased up to 1 wt. % of nanofiller content and marginally decreased thereafter. Impact strength increased with increase in nanofiller content and was attributed to cavitation at the polymer-particle boundaries. Impact strength increased to about 200% upon addition of 3 wt. % of nanofiller. TEM studies indicated good dispersion of nanofiller at 1 wt. % and agglomeration at 3 wt. % of nanofiller content. Nanocomposites had lower thermal stability than pristine polymer.